Traumatic indigestion in dairy cattle in rural KIsoro district (Makerere University Journal of Agricultural & Environmental Sciences, 2004)
Cattle (Bos sp.) are not selective feeders and often ingest foreign objects that cause traumatic injury in their forestomachs that result in indigestion, loss of production and death. However, the prevalence of this problem especially in rural areas is largely unknown. Traumatic indigestion in frequently encountered in industries countryside and is a major disease in intensively kept dairy cattle. There was need to investigate the prevalence of traumatic indigestion in rural areas. A study relying on clinical examination and use of a metal detector was conducted on herds under semi-zerograzing, zerograzing and open grazing systems in KIsoro district. Results showed that 24% of the dairy cows sampled had ingested metals with some degree of indigestion. Prevalence of metal ingestion was 61% in semi-zerograzed, 57% in zerograzed and 12% in open grazed cows. Fifteen cows received murmen magnets orally administered by a balling gun. Ten cows were operated upon with removal of various metals and other foreign objects, most spectacular being a-two by two meter cotton cloth. Agricultural extension workers, farmers and veterinarians need to emphasize the importance of preventive procedures such as sorting out cattle feeds carefully, provision of mineral salts and administration of rumen magnets to minimise occurrence of traumatic indigestion and subsequently optimum production.
Keywords: Bos sp.; reticuloperitonitis; rumnenotomy; zerograzing